Impact of Social Media Marketing on Fashion Industry in Italy - Romano, Anna (International Journal of Fashion and Design, 2023)
Purpose: The study sought to analyze impact of social media marketing on fashion industry in Italy Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that Social media has done a number of incredible things for the fashion industry, including creating fashion icons, heavily influencing fashion trends and ultimately reforming the way people go about seeking jobs in the field. Social media have turned from a simple communication tool into a huge power that influences many industries. And fashion is one of the most intertwined niches. Social platforms impact fashion, changing trends and setting the mood for haute couture and mass market segments. Unique Contribution to Theory, Practices and Policies: McLuhan's media theory and Chaffey's may be used to anchor future studies in the Fashion design sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management of fashion industries in the country will also use the study findings to improve social media coverage performance in all their activities and programs. The study recommends that the adoption of effective fashion development policies in the media will help to improve efficiency in their major operations and activities.